Impact of Organizational Factors on Employee Retention in Nepalese Banks - Kandel, Madan (NCC Journal, 2024)
This study examines the impact of compensation, career opportunities, and organizational prestige on employee retention within Nepalese commercial banks. High turnover rates in these banks disrupt operations and increase costs, necessitating effective retention strategies. Using a quantitative approach, the study surveyed 226 employees from Prime Bank and Global IME Bank in the Kathmandu Valley. Results reveal that competitive compensation is crucial for retaining lower-level employees, career opportunities are essential for those with higher education, and organizational prestige significantly influences new hires. The study highlights the need for banks to address these factors to improve retention rates and organizational performance. Limitations include the focus on two banks and potential biases from convenience sampling. Future research should broaden the scope to include more banks and explore additional variables affecting retention.